Correlation between muscle strength, joint range of motion and functionality in women after breast cancer surgery (Research, Society and Development, 2023)
Objective: to analyze the correlation between joint range of motion, muscle strength and functionality of the upper limb ipsilateral to the affected breast in the post-surgical period of women diagnosed with Breast cancer. Method: Cross-sectional study of data obtained after surgery from 22 women undergoing breast cancer treatment at Hospital João de Barros Barreto in Belém-PA. Socio-demographic data, clinical characteristics, practice of physical activities, muscle strength, range of joint movement and functionality of the upper limbs were evaluated. Results: 60% of the sample was aged ≥ 40 years old. The mean range of motion was 165.4º, 164.8º, 44º, 89.3º, 88.2º and the mean muscle strength was 5.54 kg, 9.60 kg, 7.67 kg, 5.56 kg, 4.78 kg (for flexion, abduction, extension, internal rotation and external rotation, respectively). Adjusted R² and F Test values for functionality were 0.594 and 16.4, respectively, in relation to abduction muscle strength and range of motion for external rotation. Conclusion: The study demonstrated that the best correlation model for range of motion and shoulder muscle strength in relation to functionality corresponded to a decrease in range of motion for external rotation and muscle strength for abduction. Thus, the model can predict a 59% increase in upper limb disability in breast cancer patients after surgical treatment.